Is the hero’s journey ethical? - Koh, Jia Ling. (2011)
This essay examines the tropes of the hero’s journey home, and his quest to protect home, as portrayed by Hollywood (using the blockbusters Inception (2010) and Star Trek (2009), as well as in the art house film Letters from Iwo Jima (2006) as a reference), and studies the ethics of the hero and his journey: to see if the hero is indeed heroic, or ethical. In this essay, ethics does not concern itself with power or knowledge or even morality; rather, it is ethics as defined by Emmanuel Levinas to be the first principle of being—to be responsible for the Other that is not myself. It argues that the hero's journey should not be positively presumed as a right or an obligation; nor should they be taken as a show of the triumph of the human spirit as they are wont to be; rather, they are ethical questions to be posed in terms of how the hero treats the Other, especially when the Other is the enemy.